PALYNOLOGICAL STUDY OF SOIL SAMPLE COLLECTED FROM AN ARCHAEOLOGICAL SITE (GULABI BAGH) IN LAHORE, PAKISTAN - G. Khola; U. Hanif (Journal of Animal and Plant Sciences, 2012)
Soil samples collected from an archaeological site Gulabi Bagh Lahore to  evaluate  pollen morphology and  type of pollen present in  the surface soil or their origin either they belong to vegetation of the same area or somewhat migrated. For that purpose soil was collected from 2 feet deep of the ground on 17th November 2008. Standard methods were used for the treatment of soil samples and slides were prepared. The results indicated total 10 pollen taxa in the soil sample belonging to 9 families and 10 genera. Among them nine were introduced or cultivated and only one belonging to the natural vegetation. The shapes of pollen were mostly prolate and spheroidal. Polyporate number of aperture and porate type of aperture was characteric in all the pollen taxa except one in Jatropha curcas Linn.which was non aperturate. It was also observed that  maximum pollen size was recorded in Murraya koenigii (Linn.) Spreng. and the minimum pollen size was observed in Imperata cylindrica (Linn.) P. Beauv.
Keywords: Gulabi Bagh; Palynological data; Standard; Prolate; Polyporate; Aperturate